Language Anxiety Experienced by English Department Freshmen of Wijaya Kusuma University Surabaya - Surjowati, Ribut; Sujannah, Wahyu Diny; Wirawati, Bekti (NOBEL: Journal of Literature and Language Teaching, 2022)
This research aims to describe the language anxiety level and type frequently experienced by English Department first-year students of Wijaya Kusuma University Surabaya. It used a case study as the research design to explain the phenomenon observed. The research participants were twenty-eight English Department first-year students of Wijaya Kusuma University Surabaya. Each of them was given a five-point Likert scale questionnaire adapted from Foreign Language Classroom Anxiety Scale developed by Horwitz et al. (1986). The findings unveiled that most first-year students experienced moderate language anxiety levels in which they frequently experienced the fear of negative evaluation. It is suggested that future researchers explore the students’ anxiety levels and types by considering their learning proficiency and habit.